LATIN AND INTRODUCTION TO DECLENSIONS (Journal of Universal Science Research, 2024)
Latin is a classical language known for its grammar and declensions. This comprehence and guide the world of latin declensions providing an indepth understanding the fundamentals of language. There are maily 5 types of declensions in the latin language which are further mentioned and explained separately in the article.